Comparison of modulation strategies for enhancing the photocatalytic water splitting performance of metal-organic frameworks. (April 2023) - Wang, Tao; Guo, Changyan; Zhang, Li; Zhang, Liugen; Cao, Xianglei; Akram, Naeem; Niu, Yanan; Wang, Jide
Abstract: Metal-organic framework materials (MOFs) have proven to be an excellent catalyst, but how to further improve their photocatalytic performance has become a challenge for researchers. In this study, we focus on the effect of two modulation strategies on the photocatalytic performance of MOFs, and 2-mercaptobenzimidazole (MBI) was introduced into the ZIF-67 structure by the solvent-assisted ligand exchange (SALE) method and the mixed ligand method, respectively, to modulate their photocatalytic performance. It was found that both strategies can successfully introduce MBI into the ZIF-67 structure, but the mixed ligand method tends to destroy the crystal morphology and structure of ZIF-67 and constructs a good deal of mesopores in the structure, which is detrimental to the improvement of catalytic performance. On the contrary, the SALE strategy can maintain the special crystal morphology and structure of ZIF-67 while introducing MBI, and can construct a suitable number of defects to enhance the photogenerated carrier transfer and separation efficiency of ZIF-67. Under the action of visible light, the ZIF-67- MBI catalysts obtained by the SALE method have the optimal photocatalytic activity, and their photocatalytic hydrogen and oxygen evolution rates can reach 6.14 mmol g −1  h −1 and 210 mmol g −1  h −1, respectively. This study demonstrates that the SALE method is a viable strategy to modulate the photocatalytic performance of MOFs and provides a reference for the construction of composites with excellent photocatalytic properties. Highlights: 2-mercaptobenzimidazole was introduced to modulate the performance of ZIF-67. The effect of two modulation strategies was studied comparatively. The mixed ligand method tends to destroy the crystal morphology and structure of ZIF-67. The solvent-assisted ligand exchange method was proved to be a viable strategy. The photocatalytic hydrogen evolution rates can reach 6.14 mmol g −1  h −1 .